Land and schooling: transferring wealth across generations - Quisumbing, Agnes R.; Estudillo, Jonna P.; Otsuka, Keijiro (International Food Policy Research Institute, 2003)
The authors of this book identify the factors affecting land inheritance and schooling across generations in the Philippines, Indonesia, and Ghana—countries with very different social and cultural traditions. Based on household surveys at each site, the authors examine how these factors affect the distribution of income and spending in the household as a whole and among its individual members. They look at how these differences in land holdings and education affect what sons and daughters will earn over their lifetimes. To help right gender imbalances, the authors consider policies to encourage adoption of labor-intensive agricultural technologies, to extend and strengthen school systems in rural areas, to promote competition in off-farm labor markets, and to eliminate discrimination against women. The authors conclude that there is no conflict between policies to enhance the efficiency of investments in land and human capital and policies to promote gender equity. -- from Web Abstract"